NATURE AND FUNDING OF THE INFORMAL APPRENTICESHIP SCHEME IN PORT HARCOURT, RIVERS STATE - Jaja, Atuwokiki Sam (European Scientific Journal, ESJ, 2014)
This paper focused on the nature and financing of the informal apprenticeship scheme in Port Harcourt Metropolis. A total of 1080 respondents (360 masters craftsmen/women and 720 apprentice) were randomly drawn from 18 different trades in Port Harcourt City and Obio/Akpor Local Government Areas of Rivers State. A questionnaire tagged ‘Assessment of the Management of the Informal Apprenticeship Scheme (AMIAS)’ was used for the collection of data it consisted of 19 items and contained five sections. The reliability of the instrument was determined using the test retest method, with Pearson Product Moment Correlation Coefficient reliability of 0.65. The data gathered were used to answer four research questions and three hypotheses using frequency, percentages, mean, standard deviation and z-test statistical tools at 0.05 level of significance. The study revealed that majority of master craftsmen/women and apprentices have secondary school certificates, also the gender distribution existing amongst participants of the scheme consisted of more males than females. The study also revealed that the majority of participants in the scheme usually obtain funds through loans, proceeds from the business and fee payments by apprentices. Some of the most intense challenges facing the scheme included funding, inadequate workshop space and absence of stable electricity supply. Based on the findings the researchers recommended the use of curriculum and syllabus that will enable students attend apprenticeship training at trade centers. The provision of stable electricity, grants, loans, credits and incentives such as provision of training equipment should be made available to motivate participants of the scheme.